2018
DOI: 10.1159/000493542
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Esophageal Compression on Goiter Symptoms before and after Thyroid Surgery

Abstract: Introduction: Benign nodular goiter may be associated with swallowing difficulties, but insight into the associated pathophysiology is limited. The aim of this study was to investigate the effect of surgery on the degree of esophageal compression, and its correlation to swallowing difficulties. Methods: Esophageal compression and deviation were evaluated blindly on magnetic resonance imaging (MRI) of the neck, prior to and 6 months after thyroid surgery for symptomatic benign goiter. Goiter symptoms and swallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Most of the included studies (Tables 2 , 3 ) were small, with 60 or fewer individuals in 14 of the 27 studies. Only one study applied randomization ( 15 ) and three studies used some blinding of participants, personnel or the evaluated outcomes ( 25 , 30 , 31 ). There were five observational studies, 17 studies investigating the impact of thyroidectomy, and five retrospective studies with two studies investigating thyroidectomy (Tables 2 , 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the included studies (Tables 2 , 3 ) were small, with 60 or fewer individuals in 14 of the 27 studies. Only one study applied randomization ( 15 ) and three studies used some blinding of participants, personnel or the evaluated outcomes ( 25 , 30 , 31 ). There were five observational studies, 17 studies investigating the impact of thyroidectomy, and five retrospective studies with two studies investigating thyroidectomy (Tables 2 , 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Affection of the esophagus was a common finding among patients with goiter (Table 2 ). Four studies evaluated, by chest X-ray, CT, or MRI, the prevalence of esophageal compression and/or deviation in patients undergoing thyroidectomy ( 8 , 16 , 24 , 25 ). A study of 198 patients found esophageal deviation in 14% of individuals, and esophageal compression in even fewer (8%) ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations